Understanding the nexus between traditional brick-making, biophysical and socio-economic environment of Goma Division, Mukono Municipality, Central Uganda - Turyahabwe, Remigio; Andama, Edward; Mulabbi, Andrew; Nakiyemba , Alice (Journal of Degraded and Mining Lands Management, 2024)
This study aimed to evaluate the environmental and socio-economic impact of traditional brick-making in Goma Division. The research methods included semi-structured questionnaires, key informant interviews, field observation, and focused group discussions. The results indicated that traditional brick-making is causing harm to the biophysical environment in the form of the degradation of wetland vegetation and deforestation (100%), landscape deformation (85%), air and water pollution, whereby DO had reduced by 19.8%, BOD, pH, TSS, TDS, EC and turbidity had increased by 3.8±0.9 ppm, 1.2±0.1, 89.4±0.1 mg/L, 18±0.9 ppm, 70±0.7 µS/cm, and 264±44 NTUs, respectively. Water pollution loads varied from point to point of sampling significantly at p<0.05, with the highest loads found at the tail end or downstream of the site but lowest at a point upstream of the clay mining site. The socio-economic analysis showed that the benefits of brick-making outweigh the costs in terms of magnitude, except for the frequency of responses. All respondents indicated that brick-making had created employment, while 87% reported an improvement in their standard of living. However, the activity is associated with accidents that can result in loss of life or bodily injury. It was concluded that Mukono Municipal Environmental Officers should monitor brick-making mines and site activities to prevent the creation of open pits and caves. The environment should be treated as a borrowed asset to ensure sustainability. The study suggests that financial support and awareness should be available to clay miners and brickmakers to ensure sustainability.